2003
DOI: 10.1111/j.1432-2277.2003.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic amino-acid metabolism in liver cirrhosis and in the long-term course after liver transplantation

Abstract: (2) improved liver function compared with that in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Examples of diseases in which the levels of AAA are increased and the levels of BCAA decreased are non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, cirrhosis, viral hepatitis, chronic hepatitis, biliary disease, primary biliary cirrhosis, sclerosing cholangitis and fulminant hepatic failure. Interesting results were obtained by Tietge et al [3,24]. Patients with cirrhosis had increased levels of plasma AAA and these levels correlated with the progression of the liver disease.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Examples of diseases in which the levels of AAA are increased and the levels of BCAA decreased are non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, cirrhosis, viral hepatitis, chronic hepatitis, biliary disease, primary biliary cirrhosis, sclerosing cholangitis and fulminant hepatic failure. Interesting results were obtained by Tietge et al [3,24]. Patients with cirrhosis had increased levels of plasma AAA and these levels correlated with the progression of the liver disease.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to AAA and BCAA, disturbances in the metabolism of other amino acids can be observed in patients with liver disease. Morgan et al [25] observed increased levels of plasma methionine in patients with chronic liver disease, and Tietge et al [3] in patients with cirrhosis. After liver transplantation, the levels returned to normal [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential mechanism catalyzing membrane alterations of erythrocytes in vivo is an increased concentration of proteolytic metabolites in advanced cirrhosis. 43 In addition, the synthesis of erythrocellular galactosyl-and galactosamine-containing lipids and proteins, as well as their correct glycosylation, is altered in liver cirrhosis, because many of these components are produced by hepatocytes. 1,4 These membrane alterations can lead to microscopically visible pathological shape changes, such echinocytosis and acanthocytosis (spur cells).…”
Section: Discussionmentioning
confidence: 99%
“…In children, there is little information regarding the impact of OLT on BCAA metabolism. However there is evidence that plasma concentrations of the BCAA remain depressed after OLT, whereas aromatic amino acid concentrations are usually normal, suggesting that BCAA requirements may be increased post-OLT (3)(4)(5).…”
mentioning
confidence: 99%